SGLT-2i and Risk of Malignancy in Type 2 Diabetes: A Meta-Analysis of Randomized Controlled Trials - Shi, Nanjing; Shi, Yetan; Xu, Jingsi; Si, Yuexiu; Yang, Tong; Zhang, Mengting; Ng, Derry Minyao; Li, Xiangyuan; Xie, Fei (Frontiers in Public Health, 2021)
Background: Currently, the association between sodium-glucose cotransporter 2 inhibitor (SGLT-2i) and malignancy risk has yet to be fully elucidated. This meta-analysis aimed to determine the relationship between SGLT-2i and malignancy risk in type 2 diabetes (T2D) patients. Methods: We searched PubMed, ScienceDirect, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science to identify randomized controlled trials (RCTs) published up to August 2020 related to T2D patients treated with SGLT-2i vs. placebo or other hypoglycemic agents. The meta-analysis's primary outcome was malignancies' incidence, and the results were evaluated using risk ratio (RR) and 95% confidence interval (CI). Results: We reviewed 76 articles (77 RCTs), comprising 45,162 and 43,811 patients in SGLT-2i and control groups, respectively. Compared with the control group, SGLT-2i had no significant association with augmented overall malignancy risk in T2D patients (RR = 1.05, 95% CI = 0.97–1.14, P = 0.20), but ertugliflozin may upsurge the risk (RR = 1.80, 95% CI = 1.02–3.17, P = 0.04). Compared with active hypoglycemic agents, dapagliflozin may increase (RR = 2.71, 95% CI = 1.46–6.43, P = 0.02) and empagliflozin may decrease (RR = 0.67, 95% CI = 0.45–0.98, P = 0.04) the malignancy risk. Compared with placebo, empagliflozin may exhibit risk increase (RR = 1.25, 95% CI = 1.05–1.49, P = 0.01), primarily in digestive system (RR = 1.48, 95% CI = 0.99–2.21, P = 0.05). Conclusions: Our results proposed that in diverse comparisons, ertugliflozin and dapagliflozin seemed to increase the malignancy risk in T2D patients. Empagliflozin may cause malignancy risk reduction compared with active hypoglycemic agents but increase overall risk primarily in the digestive system compared with placebo. In short, the relationship between SGLT-2i and malignancy in T2D patients remains unclear.